Political Promises in the Lens of Islamic Theology and Jurisprudence: A Case Study of Surabaya Mayor Election 2020 - Sholeh, M. Asrorun Niam (Walisongo: Jurnal Penelitian Sosial Keagamaan, 2020)
This research studied the status of political promises declared by Mayor candidates of Surabaya election 2020 during their campaigns started from September 26, 2020. It was field-library research with qualitative analysis. Data were collected by observing online media that particularly reports the election's campaign activities. They were then analyzed by using Islamic theology and jurisprudence approaches combined with structural-functionalism, symbolic interactionism, and social contract theories. It found four main remarks: first, Quranic verses and Prophetic traditions as theological underpinnings have definitely guided moral standards of Islamic politics, especially how to make such political promises. Secondly, the political realism of promises is a language of transactional politics and communication practice. Thirdly, political promises could only be legitimated by fulfilling strike pre-requirements and within very urgent conditions. Finally, the legal status of political promises must be contextual and conditional.